"Rinse and trickle": a protocol for TEM preparation and investigation of inorganic fibers from biological material. (2nd July 2016) - Vigliaturo, Ruggero; Capella, Silvana; Rinaudo, Caterina; Belluso, Elena
Abstract: The purpose of this work is to define a sample preparation protocol that allows inorganic fibers and particulate matter extracted from different biological samples to be characterized morphologically, crystallographically and chemically by transmission electron microscopy-energy dispersive spectroscopy (TEM-EDS). The method does not damage or create artifacts through chemical attacks of the target material. A fairly rapid specimen preparation is applied with the aim of performing as few steps as possible to transfer the withdrawn inorganic matter onto the TEM grid. The biological sample is previously digested chemically by NaClO. The salt is then removed through a series of centrifugation and rinse cycles in deionized water, thus drastically reducing the digestive power of the NaClO and concentrating the fibers for TEM analysis. The concept of equivalent hydrodynamic diameter is introduced to calculate the settling velocity during the centrifugation cycles. This technique is applicable to lung tissues and can be extended to a wide range of organic materials. The procedure does not appear to cause morphological damage to the fibers or modify their chemistry or degree of crystallinity. The extrapolated data can be used in interdisciplinary studies to understand the pathological effects caused by inorganic materials.